2009
DOI: 10.4271/2009-24-0060
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intake Temperature in a Turbocharged Multi Cylinder Engine operating in HCCI mode

Abstract: The operating range in HCCI mode is limited by the excessive pressure rise rate and therefore high combustion induced noise. The HCCI range can be extended with turbocharging which enables increased dilution of the charge and thus a reduction of combustion noise. When the engine is turbocharged the intake charge will have a high temperature at increased boost pressure and can then be regulated in a cooling circuit. Limitations and benefits are examed at 2250 rpm and 400 kPa indicated mean effective pressure. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…29,30 Third, the compression ignition process is dominantly controlled by the chemical kinetics of the fuel, especially via the intake temperature, which plays an important role on cyclic variations in CA50. 12,25,31 Fourth, as Saxena and Bedoya 32 concluded, cyclic variations in HCCI combustion are mainly produced by fluctuations in the charge temperature and composition, and combustion is more sensitive to small variations in the compressed gas temperature. Perturbations of the compressed gas temperature can be induced by variations in the temperature and composition of the intake charge, residual gas, and EGR gas, as well as heat transfer losses and cooling of fuel injected in the intake port for RCCI engines.…”
Section: Computational Model and Validationmentioning
confidence: 97%
See 1 more Smart Citation
“…29,30 Third, the compression ignition process is dominantly controlled by the chemical kinetics of the fuel, especially via the intake temperature, which plays an important role on cyclic variations in CA50. 12,25,31 Fourth, as Saxena and Bedoya 32 concluded, cyclic variations in HCCI combustion are mainly produced by fluctuations in the charge temperature and composition, and combustion is more sensitive to small variations in the compressed gas temperature. Perturbations of the compressed gas temperature can be induced by variations in the temperature and composition of the intake charge, residual gas, and EGR gas, as well as heat transfer losses and cooling of fuel injected in the intake port for RCCI engines.…”
Section: Computational Model and Validationmentioning
confidence: 97%
“…The relatively independent behavior among the cyclic variations in different parameters has also been observed in experiments of HCCI combustion. Previous experiments 12,25,26 indicated that it is effective to utilize the cyclic variations in ignition timing to control the overall stability of HCCI combustion. Since the cyclic variations in CA50 dramatically affect the emissions, noise, and variability of RCCI combustion, 18 this study focused on the cyclic variations in ignition timing using the STD of CA50 as the metric.…”
Section: Computational Model and Validationmentioning
confidence: 99%
“…With NVO the intake temperature directly affects how much internal EGR is needed for a given combustion timing and therefore the in-cylinder relative burn gas fraction. By increasing the intake temperature, less internal EGR is needed which lead to increased mass flow that can lead to higher boost pressure [12]. In addition to the internal EGR, external cooled EGR can be used and it was found that it could improve combustion efficiency while there seem to be low influence on the combustion duration [13] in HCCI mode.…”
Section: Introductionmentioning
confidence: 99%
“…The CA50 timing will affect the engine performance substantially and need to be controlled exactly to run the HCCI engine successfully. If engine speed goes up or if load is increased the CA50 window for stable engine operating will be narrowed [12], making the engine control more challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation